CHYLOPERITONEUM AFTER GASTRECTOMY: IS IT A MANAGEABLE NIGHTMARE? - Castro, Bárbara (2024)
Chylous ascites is a serious and rare complication after gastrectomy for gastric cancer. Most cases improve with conservative treatment, but substantial morbidity and mortality can be associated. We describe the case of a 48-year-old-male submitted to partial gastrectomy with D2 lymphadenectomy for gastric adenocarcinoma. Three days after starting a liquid diet, it was diagnosed a chyle fistula. Conservative treatment was started with improvement of the patient and he was discharged. After eighteen days, the patient was readmitted due to a large volume chyloperitoneum, requiring paracentesis. Medical treatment was reinstituted, with amelioration and dismissal of the patient. The patient returned to the emergency department due to abdominal pain and fever and was submitted to laparoscopic abdominal drainage. There was resolution of refractory ascites during hospitalization. Chylous ascites is a rare complication after radical resections for gastric cancer. Therefore, there is no well-defined treatment and these cases remain a therapeutic challenge. The therapeutic strategies described include dietary measures, the use of pharmacological agents, total parenteral nutrition and, in selected cases, surgical or percutaneous interventions.